KERAGAMAN BEBERAPA SIFAT KIMIA DAN BIOLOGI TANAH PADA BERBAGAI TIPE PENGGUNAAN LAHAN RAWA LEBAK - GOFAR, NUNI (AGRITROP; Vol. 26, No. 2 Juni 2007)
The purposes of this study were to study: 1) the influence of agricultural land use on some swamp soil chemical (soil pH, Organic C content, N-total, and P-total) and biological (population of bacteria, fungi, and actinomycetes) properties, and 2) correlation between soil microbial population and Organic C content, N-total as well as P-total. Based on the results of field observation, it was determined 6 plant commodities with different length of land use as treatments and secondary forest as control. The results of this study showed that: 1) Differences in land use resulted in different soil chemical (soil pH, Organic C content, N-total, and P-total) and biological (population of bacteria, fungi, and actinomycetes) properties, 2) Soil organic C, N-total and P-total content together significantly affected on population of bacteria and fungi, but did not affected on actinomycetes population. The magnitudes of Soil organic C, N-total and P-total influence on bacteria, fungi, and actinomycetes population were 69,8 %, 59,8 % and 49,7 %, respectively, 3) as soil organic C and P-total contents were constant, soil N-total content significantly affected on population of bacteria and fungi, but did not affected on actinomycetes population, 4) Population of bacteria, fungi and actinomycetes was highly correlated with soil organic C and N-total content, but was not correlated with soil P-total content, 5) the most microbial variation was found on soil collected from rubber plantation, followed by orange and secondary forest.
Keywords: chemical and biological properties, swampy soil, types of land use